Distribution of the integral membrane protein NADH-cytochrome b5 reductase in rat liver cells, studied with a quantitative radioimmunoblotting assay. - Borgese, N (1986)
The intracellular localization of the post-translationally inserted integral membrane protein, NADH-cytochrome b5 reductase, was investigated, using a quantitative radioimmunoblotting method to determine its concentration in rat liver subcellular fractions. Subcellular fractions enriched in rough or smooth microsomes, Golgi, lysosomes, plasma membrane and mitochondrial inner or outer membranes were characterized by marker enzyme analysis and electron microscopy. Reductase levels were determined both with the NADH-cytochrome c reductase activity assay, and by radioimmunoblotting, and the results of the two methods were compared. When measured as antigen, the reductase was relatively less concentrated in microsomal subfractions, and more concentrated in fractions containing outer mitochondrial membranes, lysosomes and plasma membrane than when measured as enzyme activity. Rough and smooth microsomes had 4-5-fold lower concentrations, on a phospholipid basis than did mitochondrial outer membranes. Fractions containing Golgi, lysosomes and plasma membrane had approximately 14-, approximately 16, and approximately 9-fold lower concentrations of antigen than did mitochondrial outer membranes, respectively, and much of the antigen in these fractions could be accounted for by cross-contamination. No enzyme activity or antigen was detected in mitochondrial inner membranes. Our results indicate that the enzyme activity data do not precisely reflect the true enzyme localization, and show an extremely uneven distribution of reductase among different cellular membranes.